Serum Metabolomic Profiling in Rheumatoid Arthritis Patients With Interstitial Lung Disease: A Case–Control Study - Furukawa, Hiroshi; Oka, Shomi; Shimada, Kota; Okamoto, Akira; Hashimoto, Atsushi; Komiya, Akiko; Saisho, Koichiro; Yoshikawa, Norie; Katayama, Masao; Matsui, Toshihiro; Fukui, Naoshi; Migita, Kiyoshi; et al. (Frontiers in Medicine, 2020)
Objectives: Interstitial lung disease (ILD) is an extra-articular manifestation in rheumatoid arthritis (RA), detected in 10.7% of patients, and causing a poor prognosis. Hence, biomarkers for ILD are urgently required in RA. Low molecular weight metabolites can be assessed by metabolomic analyses, and although these have been conducted in RA and in idiopathic pulmonary fibrosis, few have been carried out for ILD in the context of RA. Therefore, we analyzed serum metabolomic profiles of ILD in RA to identify novel biomarkers. Methods: Serum samples from 100 RA patients with ILD and 100 matched RA patients without chronic lung disease (CLD) were collected. These samples were subjected to metabolomic analyses using capillary electrophoresis time-of-flight mass spectrometry. Results: A total of 299 metabolites was detected in the metabolomic analysis By univariate analysis, serum levels of decanoic acid and morpholine were lower in RA with ILD (false discovery rate Q=1.87X10-11 and 7.09X10-6, respectively), and glycerol was higher (Q=1.20X10-6), relative to RA without CLD. Serum levels of these metabolites in RA with usual interstitial pneumonia or RA with nonspecific interstitial pneumonia were also altered. The partial least squares-discriminant analysis model generated from these three metabolites could successfully discriminate ILD in RA (area under the curve: 0.919, 95% confidence interval: 0.867-0.968, sensitivity 0.880, specificity 0.780). Conclusions: Serum levels of some metabolites were significantly different in RA with ILD compared to RA without CLD. It is concluded that metabolomic profiling will be useful for discovering candidate screening biomarkers for ILD in RA.